2018
DOI: 10.1186/s12873-018-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergency response time and pre-hospital trauma survival rate of the national ambulance service, Greater Accra (January – December 2014)

Abstract: BackgroundEvery year, about 1.2 million people die through road traffic crashes worldwide. Majority of these deaths occur in Africa where most of their emergency medical services are underdeveloped. In 2004, Ghana established the National Ambulance Council to provide timely and efficient pre-hospital emergency medical care to the sick and injured. Pre-hospital emergency medical service is essential for accident victims since it has the potential of saving lives. The study sought to determine the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 14 publications
(12 reference statements)
3
33
2
1
Order By: Relevance
“…The current study also reports that ACN is associated with shorter times to hospital arrival among less urban areas, though these times are still over the 30-minute threshold of increased mortality risk reported by Plevin et al (2017). Literature on the effect of transport time on trauma mortality reports are mixed, with studies out of Perth, Western Australia and South Korea reporting lower mortality for longer transport times and a study in Ghana reporting higher mortality among all-cause trauma (Brown et al 2019, Kim et al 2017, Mahama et al 2018. Despite this, research has reported that longer pre-hospital times are associated with an increased likelihood of more intensive interventions during the initial trauma resuscitation periods; as a result, it is possible that the effects of ACN availability of decreased pre-hospital times, particularly among rural areas, may result in decreased likelihood of escalation of care, resulting in more beneficial clinical outcomes such as shorter length of hospital stay and cost of care.…”
Section: Discussionmentioning
confidence: 50%
“…The current study also reports that ACN is associated with shorter times to hospital arrival among less urban areas, though these times are still over the 30-minute threshold of increased mortality risk reported by Plevin et al (2017). Literature on the effect of transport time on trauma mortality reports are mixed, with studies out of Perth, Western Australia and South Korea reporting lower mortality for longer transport times and a study in Ghana reporting higher mortality among all-cause trauma (Brown et al 2019, Kim et al 2017, Mahama et al 2018. Despite this, research has reported that longer pre-hospital times are associated with an increased likelihood of more intensive interventions during the initial trauma resuscitation periods; as a result, it is possible that the effects of ACN availability of decreased pre-hospital times, particularly among rural areas, may result in decreased likelihood of escalation of care, resulting in more beneficial clinical outcomes such as shorter length of hospital stay and cost of care.…”
Section: Discussionmentioning
confidence: 50%
“…Our median response time from when LASAMBUS received the call to when they arrived on the scene (17 min) was comparable to the response time of ambulances in Accra, Ghana and is only 2 min longer than the median urban response time across all African EMS systems [15,27]. Lower response times have been shown to be associated with better patient outcomes and higher chances of survival and is a crucial part of pre-hospital care management [27]. Findings from a study conducted in Spain in 2010 estimated that a 10 min reduction in response time could result in a 33% decrease in mortality rates in RTAs [28].…”
Section: Discussionmentioning
confidence: 71%
“…Another important factor to consider in our study is the mean time of patient arrival to the ED from the time of incident which was 3 h. This is much longer than what is documented internationally in places with good prehospital facility. [14] The reasons for this time lag are a substandard prehospital service in India and our hospital being a tertiary care referral center. According to Holford, alcohol follows a one-compartment model with concentration-dependent elimination.…”
Section: Discussionmentioning
confidence: 99%